Curation and collaboration as activism: emerging critical practices of #FemEdTech. Issue 1 (2nd January 2022) - Beetham, Helen; Drumm, Louise; Bell, Frances; Mycroft, Lou; Forsythe, Giulia
ABSTRACT: The inequities rooted in our education systems and wider societies have been thrown into relief by responses to the COVID-19 pandemic. This paper presents four situational studies of the FemEdTech network, asking how we characterise activities of the network, what they tell us about the nature of diffuse, convivial networks, and what opportunities they provide for challenging inequities in the field of technology and/in education. The study draws on practices and materials produced through FemEdTech activities from 2017 to 2020. Data and its analysis are presented as a spiral of 'turns' which fold back on each other to create connections between lines of research, moving fluidly between the objective and subjective. The four studies present shared curation, collaborative writing and purposeful reflection as contested fields of action. On one hand they build solidarity and shared resources – 'holding up' the flow of knowledge in networks, potentially redistributing the capital of attention and connectivity. At the same time, they underscore the costs of shared work which are different in open networks from those that operate in the reified, accelerated production cycles of academic roles – yet connected with them, not least because they always involve investments of care.